Techno-Economic Analysis of a Grid-Connected Hybrid PV/Wind Power System- Case Study at Leh Ladakh in India (International Journal of Innovative Research in Engineering & Management, 2021)
The national grid is able to provide round the clock energy supply.  Some region of India owing their geographical not able to get  continuous power supply from the grid, one such location is Leh.  The power delivered in that region is of very low quality, having  frequent outage and the reliability of the supply becomes a  challenge. During harsh environment the supply and reliability  affected greatly due to the restricted movement of man and  material. On the other hand, renewable energy supply being  located on the site of installation can be able to eliminate such  challenges. Hybrid combination of PV and Wind along with some  storage facilities can mitigate the challenges. The storage battery  increases the project cost and also releases pollutants during their  operation. So the study uses the existing national grid to exchange  the energy, the combination of PV-wind with the national grid.  The study finds out the optimal size of such combination,  focusing on the reliability and cost effective energy supply.
Keywords: Hybrid; Technical; Economic; Photovoltaic; Wind; Net Present Cost